Challenges in Improving the Services of La Union Electric Cooperative Incorporated (LUELCO, Inc.) For Member-Consumer-Owners’ (MCOS) Satisfaction In The Province of La Union - Medina, Glades; Martin, Jr. , Narciso A.; Posadas, Ramon (Southeast Asian Journal of Science and Technology, 2020)
The study used descriptive-correlational research methodologies because it described the satisfaction delivered by LUELCO employees and established the relationship of the challenges encountered by a registered consumer in the field of electrification. The total sampling comprised 120 Member-Consumer-Owners (MCOs) from the six (6) service branches of LUELCO in the Province of La Union and they were taken randomly. The study had a hundred percent retrieval rate. Mean, weighted mean, rankings and Pearson Product-Moment Correlation Coefficient were used to present and interpret the results. Data revealed that the actual service (4.24) experienced by Member-Consumer-Owners (MCOs) was less than what they expected (4.60) from LUELCO which resulted in gap scores in the service dimensions of each branch. SERVQUAL RATER confirmed that Branch F (-1.06) obtained the highest gap. Noted some indicators such as consumers’ confidence in employees (+0.40), consumers’ best interests at heart (+0.25) and personal attention by employees (+0.20) can increase satisfaction ratings from MCOs. Recommendations were provided such as increase tangibles for Branches A, E and F for branch aesthetics while enhances service contact for Branches B, C and D. The computed Pearson’s r (0.41) confirmed that the satisfaction rating of MCOs was moderately affected by the challenges. Therefore, the study strongly suggests the creation and design of MCOs Service Flowchart and adapt the proposed plan of action.